2020
DOI: 10.1080/08854726.2020.1727602
|View full text |Cite
|
Sign up to set email alerts
|

Witnesses of hope in times of despair: chaplains in palliative care. A qualitative study

Abstract: Hope is an important topic in spiritual care in palliative care but the experiences of chaplains with hope have hardly been explored. The objective of this study was to explore Dutch chaplains' experiences with hope in palliative care. Semi-structured interviews were conducted, which were thematically analyzed. The 10 chaplains had a variety of ordinations: Muslim, Protestant, Roman Catholic, Humanistic, or otherwise. Participants spoke about changes in patients' hope, often implying despair and surrender, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The notion of developing effective professional and therapeutic relationships with families attracts some practitioners into palliative and hospice care (Parola et al, 2018). Establishing therapeutic relationships with families comes at a cost to practitioners through bearing witness to the grief and sadness experienced by family members following the death of their child (Olsman, 2020).…”
Section: Family-centred Carementioning
confidence: 99%
“…The notion of developing effective professional and therapeutic relationships with families attracts some practitioners into palliative and hospice care (Parola et al, 2018). Establishing therapeutic relationships with families comes at a cost to practitioners through bearing witness to the grief and sadness experienced by family members following the death of their child (Olsman, 2020).…”
Section: Family-centred Carementioning
confidence: 99%
“…The objectives of this study were (1) to provide an overview of review studies on hope in health care and to describe (2) conceptualizations of hope, (3) antecedents and consequences of hope, and (4) ethical topics related to hope. The findings will also aid reflection on the role of spirituality in health care, since hope is a central topic in spiritual care (Capps 2001;Gijsberts et al 2019;Lester 1995;Olsman 2020).…”
Section: Introductionmentioning
confidence: 97%
“… 2 Recently, hope has been defined as a “multidimensional construct that might change over time”. 3 Hope in terminally ill patients cannot be considered merely as a coping strategy, nor dismissed simply as wishful thinking. 4 Studies investigating the antecedents of hope have shown that inspiring relationships play a significant role in generating hope and maintaining it, despite adverse circumstances.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Studies investigating the antecedents of hope have shown that inspiring relationships play a significant role in generating hope and maintaining it, despite adverse circumstances. 3 A critical aspect emerging in all the studies on hope is its connection with truth: on the one hand, healthcare professionals understand the need to sustain hope for their patients; on the other hand, they know they have an obligation to tell them the truth about their condition. This tension is particularly acute when patients must be told they are terminally ill.…”
Section: Introductionmentioning
confidence: 99%